SOME POPULATION PARAMETERS OF ENDEAVOUR SHRIMP (Metapenaeus ensis de Haan) lN BALIKPAPAN SURROUNDING WATERS, EAST KALIMANTAN - Ali Suman; Gatut Bintoro (Research Center for Fisheries, 2009)
Study on the population parameters of endeavour shrimp (Metapenaeus ensls de hlaan) was conducted in Balikpapan waters, East Kalimantan. Population parameters of the endeavour shrimp were calculated based on data collected during period of survey, March 2006-November 2006.